2014
DOI: 10.1016/j.jinorgbio.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Bioinorganic chemistry of synucleinopathies: Deciphering the binding features of Met motifs and His-50 in AS–Cu(I) interactions

Abstract: The aggregation of alpha-synuclein (AS) is a critical step in the etiology of Parkinson's disease (PD) and other neurodegenerative synucleinopathies. This process is selectively enhanced by copper in vitro and the interaction is proposed to play a potential role in vivo. Presently, the identity of the Cu(I) binding sites in AS and their relative affinities are under debate. In this work we have addressed unresolved details related to the structural binding specificity and affinity of Cu(I) to full-length AS. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…3B), consistent with previous studies. 42,50 Interestingly, the value reported for the Cu(I)-complex in the non-acetylated protein was c K d1 = 7.8 AE 1.0 nM, 48 in line with the affinity differences found for Cu(I) binding to the N-acetylated and free amine P1AS peptides. The value of c K d1 for complexation of Cu(I) to the Met-X 3 -Met site in M5I/H50A AcaS and the D2A aS were 63 AE 5 nM and 14 AE 2 nM, respectively.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…3B), consistent with previous studies. 42,50 Interestingly, the value reported for the Cu(I)-complex in the non-acetylated protein was c K d1 = 7.8 AE 1.0 nM, 48 in line with the affinity differences found for Cu(I) binding to the N-acetylated and free amine P1AS peptides. The value of c K d1 for complexation of Cu(I) to the Met-X 3 -Met site in M5I/H50A AcaS and the D2A aS were 63 AE 5 nM and 14 AE 2 nM, respectively.…”
supporting
confidence: 75%
“…NMR-based studies revealed that the main anchoring groups for Cu(I) binding -Met1/Met5 (site 1), His50 (site 2) and Met116/Met127 (site 3)-were preserved in the acetylated form of the protein 42,[47][48][49] (Fig. 1).…”
mentioning
confidence: 99%
“…These apparent affinities of Cu I for truncated or full-length aS were in the lower-mm range. [21,23,38] Thus, affinitieslower than the estimated Cu I affinities here wereobtained.…”
Section: Discussionmentioning
confidence: 95%
“…In the case of Cu I ,t he affinity of Ab remains am atter of debate, [36,37] and for aS only apparent binding constants (not taking the presence of buffer and reducing agent into account) are reported. [38] In addition, the impact of the additional Met residue in bS on the Cu I affinity is not known.…”
mentioning
confidence: 99%
“…Indeed, the catalytic oxidase activity of the AS‐Cu(II) complexes was shown to yield formation of hydroxyl radicals and AS oxidation (Wang et al ; Meloni and Vašák ). An NMR study demonstrated that the redox cycling of copper bound to AS can generate reactive oxygen species, leading to site‐specific metal‐catalyzed oxidation on methionine residues under physiologically relevant conditions (Miotto et al, , ). Met1 and Met5 residues can be oxidized rapidly (Met1 faster than Met5) to a sulfoxide species after air exposure of the AS‐Cu(I) complexes, whereas Met116 and Met127 remain unaffected (Miotto et al, , ).…”
Section: α‐Synuclein Is a Metal‐binding Proteinmentioning
confidence: 99%